A study of the usage of uses and gratification and also narcissism in social media to influence student engagement / Muhammad Azizi Yusri - Yusri, Muhammad Azizi (Faculty of Business and Management, 2018)
This study focuses on the usage of uses and gratification and also narcissism in social media that can influence student engagement. Data were gathered from a non-probability sample of 127 respondents through online tools, Google Form. Factor analysis result shown that uses and gratification is supported by few elements such as past-time, affection, fashion and sociability while narcissism is supported by authority/superior, exhibitionism, exploitativeness and vanity. In particular, people who used social media has their own need and self-satisfaction. In contrast, both uses and gratification and narcissism have their own role to engage with the student involvement. There is issue regarding these variables as they argue the function of these platforms to these users since all of them has their same commons. Throughout this study, it stated that uses and gratification is strongly correlated with the student engagement compared to narcissism. This paper includes a discussion of the study throughout the result finding and also the conclusion and recommendation for future research.